2010
DOI: 10.1007/s00787-010-0106-8
|View full text |Cite
|
Sign up to set email alerts
|

Atopic conditions and mental health problems: a 3-year follow-up study

Abstract: The aim of this study was to test the hypothesis that atopic conditions at 15/16 years of age affect both internalized and externalized mental health problems 3 years later. Combined school and postal survey was conducted in urban and rural settings. A total of 3,674 adolescents (70.1% response rate) were followed at two time points and interviewed with similar questionnaires at baseline and follow-up. Hopkins Symptoms Checklist (HSCL-10) was used to assess internalized problems, and two subscales (conduct pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
2
6
0
1
Order By: Relevance
“…Research suggests that additional comorbidity generally adds to the burden of disease [42,61]. Our results lend support to this finding, as number of conditions within an individual was linearly related to decrements in HRQoL.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Research suggests that additional comorbidity generally adds to the burden of disease [42,61]. Our results lend support to this finding, as number of conditions within an individual was linearly related to decrements in HRQoL.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies observed associations of eczema, hay fever or asthma with psychiatric conditions [38][39][40][41][42]. This is why mental health needs to be controlled for to see if there are independent associations of the respective condition with HRQoL impairments over and above that caused by mental health impairments.…”
Section: Introductionmentioning
confidence: 98%
“…김 재 희 에 부정적 영향을 주게 되므로 (Bennett, Shafran, Coughtrey, 만성신체질환이 있는 청소년들은 Walker, & Heyman, 2015), 질환이 없는 청소년에 비해 정신적 문제를 가질 가능성이 더욱 높다 몇 (Hysing, Elgen, Gillberg, Lie, & Lundervold, 2007). 몇 연구에서 천식이 정신건강과 관련이 있는 것으로 나타났 으며 (Ortega, Huertas, Canino, Ramirez, & Rubio-Stipec, 2002; 아토피 피부염 역 Van Lieshout & Macqueen, 2012), 시 정신건강의 문제를 가져올 수 있음이 확인되고 있다 (Halvorsen et al, 2014;Lien, Green, Thoresen, &…”
unclassified
“…These data were not statistically significant. In fact, Lien et al 22 found that patients with AD were more likely to have "internalizing" mental health problems (ie, feeling panicky, anxious, dizzy, sleepless, sad, worthless, hopeless), an association that was statistically significant in all sex and age groups.…”
Section: Commentmentioning
confidence: 99%